Skrining Triterpenoid dan Formulasi Granul dari Ekstrak Daun Mengkudu (Morinda Citrifolia L.) sebagai Neuroprotektor pada Perokok - Dhigna Luthfiyani Citra Pradana (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
The objective of this research was triterpenoids screening and made granules formulafrom Morindacitrifolia leaf extract as neuroprotector for smoker. Morinda citrifolia leaf extract was made by maceration using 70% ethanol. The granules of Morinda citrifolia leaf extract was composed by 3 formulas containing 10% leaf extract of Morinda citrifolia and with different levels of manitol (20% F I, F II 25%, 30%). All of formulas comply the qualification of affects fixed corner and granules flow time that base on Farmakope Indonesia. The variation of manitol concentration significantly affects fixed corner and granules flow time. The greater level of mannitol concentration 20% to 30%produced fixed corner and granules flow time of the granulesare greater.